Review of “Developing Writers in Higher Education” - Lilik Ulfiati (Universitas Jambi, Magister Program of English Education Department, 2020)
Instructors and researchers of writing in higher education often experience discouraged when they find their teaching falling short their expectation even though a number of endeavors they invest in the teaching practices and research works. As a writing teacher for higher education, I feel disappointed when I am not able to present more beneficial support than the motivation to write using appropriate vocabularies, making grammatical sentences consisted of compound or complex ones, organizing ideas of writing or paragraphs, constructing coherence essays and so on. After ineffective attempts at aiding higher education students significantly enhance their writing, I began to review the nature of writing and facets other than the language competences comprising what activities the teachers are necessary to carry out, how the students’ writing practices are applied during their writing process, who are involved in the process of writing and how long the writing activities take place. I have figured out solutions to some questions in the book entitled “Developing Writers in Higher Education”. In this five-section book, Anne Ruggles Gere describes comprehensive longitudinal study about topic concerning on how students in higher education keep practicing their writing process and their writing follow various developmental paths.